Dexamethasone Does Not Inhibit Sugammadex Reversal After Rocuronium-Induced Neuromuscular Block. (June 2016) - Buonanno, Pasquale; Laiola, Anna; Palumbo, Chiara; Spinelli, Gianmario; Servillo, Giuseppe; Di Minno, Raffaele Maria; Cafiero, Tullio; Di Iorio, Carlo
Abstract : BACKGROUND: Sugammadex is a relatively new molecule that reverses neuromuscular block induced by rocuronium. The particular structure of sugammadex traps the cyclopentanoperhydrophenanthrene ring of rocuronium in its hydrophobic cavity. Dexamethasone shares the same steroidal structure with rocuronium. Studies in vitro have demonstrated that dexamethasone interacts with sugammadex, reducing its efficacy. In this study, we investigated the clinical relevance of this interaction and its influence on neuromuscular reversal. METHODS: In this retrospective case-control study, we analyzed data from 45 patients divided into 3 groups: dexamethasone after induction group (15 patients) treated with 8 mg dexamethasone as an antiemetic drug shortly after induction of anesthesia; dexamethasone before reversal group (15 patients) treated with dexamethasone just before sugammadex injection; and control group (15 patients) treated with 8 mg ondansetron. All groups received 0.6 mg/kg rocuronium at induction, 0.15 mg/kg rocuronium at train-of-four ratio (TOF) 2 for neuromuscular relaxation, and 2 mg/kg sugammadex for reversal at the end of the procedure at TOF2. Neuromuscular relaxation was monitored with a TOF-Watch® system. RESULTS: The control group had a recovery time of 154 ± 54 seconds (mean ± SD), the dexamethasone after induction group 134 ± 55 seconds, and the dexamethasone before reversal group 131 ± 68 seconds. The differences among groups were not statistically significant ( P = 0.5141). CONCLUSIONS: Our results show that the use of dexamethasone as an antiemetic drug for the prevention of postoperative nausea and vomiting does not interfere with reversal of neuromuscular blockade with sugammadex in patients undergoing elective surgery with general anesthesia in contrast to in vitro studies that support this hypothesis. Abstract : Published ahead of print March 29, 2016